Perovskite ink, preparation method thereof and perovskite solar cell

Through the new perovskite ink system, the crystallinity and stability of perovskite films are improved by using 2-methoxyethanol and other solvents, the toxicity and stability of the DMF+DMSO solvent system are solved, and high efficiency and Environmentally friendly perovskite solar cell preparation.

CN119317341APending Publication Date: 2025-01-14GUANGDONG MINGYANG FILM TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411371289.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The DMF+DMSO solvent system used in existing perovskite solar cells has problems such as high toxicity, flammability, slow solvent volatility and poor storage stability, which affects battery life and industrial application.

Method used

A new perovskite ink system is adopted, including precursor A and precursor B, solute A and solvent A, solute B and solvent B, where solvent A is 2-methoxyethanol and solvent B is acetonitrile and N-methyl. -2-pyrrolidone, etc., by adjusting the solvent system, improve the crystallinity and stability of perovskite films and reduce toxicity.

Benefits of technology

It improves the energy conversion efficiency and stability of perovskite solar cells, reduces the toxicity of the solvent system, is friendly to the human body and the environment, simplifies the preparation process, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119317341A_ABST
    Figure CN119317341A_ABST
Patent Text Reader

Abstract

The invention provides perovskite ink, a preparation method thereof and a perovskite solar cell. The perovskite ink comprises a precursor solution A and a precursor solution B. The precursor solution A comprises a solute A and a solvent A, the precursor solution B comprises a solute B and a solvent B, the solute A comprises at least one of halogenated methylamine, halogenated formamidine, cesium halide and lead halide, and the solute B comprises at least one of cesium halide, lead halide and halogenated methylamine. The perovskite thin film prepared by using the perovskite ink is higher in crystallinity, larger in grain size after annealing and free of pinholes, and the energy conversion efficiency of the prepared perovskite solar cell is higher than that of a traditional DMF + DMSO solvent system. The invention also provides a preparation method of the perovskite ink and a perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite solar cells, and in particular relates to a perovskite ink and a preparation method thereof, and a perovskite solar cell. Background Art

[0002] Since its advent in 2009, perovskite solar cells have developed rapidly. At present, single-junction inverted perovskite solar cells have achieved an energy conversion efficiency of 26.7%, and the energy conversion efficiency of crystalline silicon-perovskite stacked solar cells has reached 34.6%. Perovskite solar cells have the advantages of high conversion efficiency, simple preparation process, low manufacturing cost, can be prepared on flexible substrates, and a wide light absorption range. They have high industrial value and are expected to cross the commercialization threshold and subvert the dominant position of crystalline silicon solar cells in the photovoltaic market. As the core component of perovskite solar cells, the perovskite absorption layer plays a decisive role in the photoelectric conversion efficiency and stability of the battery. The preparation of the perovskite absorption layer can be divided into two categories: solution method (wet preparation) and gas phase method (vacuum coating preparation) according to whether a solvent is used. At present, the perovskite solar cells prepared by the solution method have higher efficiency. Commonly used solution method preparation processes include one-step solution spin coating, two-step solution immersion, low-temperature gas-phase assisted solution method, slit coating, blade coating, spray coating, etc. In the process of preparing perovskite absorber layer by solution method, the characteristics of the solvent and the post-treatment process largely determine the crystallization process of the perovskite film.

[0003] By adjusting the solvent, the toxicity of the solvent system can be reduced, the coordination properties of the precursor can be adjusted, and the film nucleation and crystallization process can be controlled. N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) are widely used in the preparation of perovskite inks due to their strong polarity and high solubility in perovskite precursors. However, these two solvents are highly toxic and flammable, which have adverse effects on human health and the natural environment. At the same time, the DMF+DMSO solvent system as a perovskite ink has the following disadvantages: (1) The solvent evaporation rate is slow, which affects the coating quality and shortens the battery life; (2) It is easy to aggregate and crystallize, resulting in poor storage stability, thereby increasing toxic waste.

[0004] Therefore, it is necessary to develop a new solvent system through coordination regulation to minimize the use of toxic and harmful solvents while ensuring the quality of the perovskite absorption layer and ensuring the efficiency and stability of the battery, so as to achieve an environmentally friendly perovskite solar cell preparation process. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a perovskite ink, and the perovskite film prepared using the perovskite ink of the present invention has higher crystallinity, larger grain size after annealing, no pinholes, and the energy conversion efficiency of the prepared perovskite solar cell is higher than that of the traditional DMF+DMSO solvent system, the stability of the perovskite solar cell is better than that of the traditional DMF+DMSO solvent system, and the solvent system of the perovskite ink is less toxic and less harmful to the human body and the natural environment.

[0006] The invention also provides a method for preparing the perovskite ink.

[0007] The invention also provides a perovskite solar cell.

[0008] The invention also provides a method for preparing a perovskite solar cell.

[0009] The first aspect of the present invention provides a perovskite ink, the components of which include a precursor liquid A and a precursor liquid B, the precursor liquid A includes a solute A and a solvent A, the precursor liquid B includes a solute B and a solvent B, the solute A includes at least one of a methylamine halide, a methylamidine halide, a cesium halide and a lead halide, the solvent A is 2-methoxyethanol, the solute B includes at least one of a cesium halide, a lead halide and a methylamine halide, and the solvent B includes at least one of acetonitrile, N-methyl-2-pyrrolidone, 1,3-dimethyl-3,4,5,6-tetrahydro-2-pyrimidone, ethanol and 1-cyclohexyl-2-pyrrolidone.

[0010] A technical solution of the perovskite ink in the present invention has at least the following beneficial effects:

[0011] Under the same atmosphere, the perovskite film prepared using the perovskite ink of the present invention has higher crystallinity, larger grain size after annealing, and no pinholes.

[0012] Under the same cell structure, the energy conversion efficiency of the perovskite solar cell prepared using the perovskite ink of the present invention is higher than that of the traditional DMF+DMSO solvent system.

[0013] Under the same atmosphere and battery structure, the stability of the perovskite solar cell prepared using the perovskite ink of the present invention is better than that of the traditional DMF+DMSO solvent system.

[0014] Compared with the DMF+DMSO solvent system, the solvent system of the perovskite ink of the present invention is less toxic and less harmful to the human body and the natural environment.

[0015] According to some embodiments of the present invention, the concentration of the precursor solution A is 0.6-1.6 mol / L.

[0016] According to some embodiments of the present invention, the concentration of the precursor solution A is any value of 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 mol / L or a range formed by any two of them.

[0017] According to some embodiments of the present invention, the concentration of the precursor solution A is 1.0 mol / L.

[0018] According to some embodiments of the present invention, the concentration of the precursor solution B is 0.2-1.2 mol / L.

[0019] According to some embodiments of the present invention, the concentration of the precursor solution B is any value of 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 mol / L or a range formed by any two of them.

[0020] According to some embodiments of the present invention, the concentration of the precursor solution B is 0.6-1.0 mol / L.

[0021] According to some embodiments of the present invention, the volume ratio of the precursor solution A and the precursor solution B is calculated based on the perovskite composition and the precursor solution concentration.

[0022] According to some embodiments of the present invention, the solute A is selected from at least one of methylamine halides, formamidine halides, cesium halides and lead halides.

[0023] According to some embodiments of the present invention, the solute A is selected from at least one of MABr, MACl, PbI2, PbBr2, and FAI.

[0024] According to some embodiments of the present invention, the solute B is selected from at least one of cesium halide, lead halide and methylamine halide.

[0025] According to some embodiments of the present invention, the solute B is selected from at least one of PbI2, CsI, and MACl.

[0026] According to some embodiments of the present invention, the solvent B is selected from at least one of acetonitrile, N-methyl-2-pyrrolidone, 1,3-dimethyl-3,4,5,6-tetrahydro-2-pyrimidinone, ethanol and 1-cyclohexyl-2-pyrrolidone.

[0027] According to some embodiments of the present invention, the solvent B is N-methyl-2-pyrrolidone and / or acetonitrile.

[0028] The second aspect of the present invention provides a method for preparing the perovskite ink of the first aspect of the present invention, comprising the following steps:

[0029] Dissolving the solute A in the solvent A to obtain the precursor solution A;

[0030] Dissolving the solute B in the solvent B to obtain the precursor solution B;

[0031] The precursor solution A and the precursor solution B are mixed to obtain the perovskite ink.

[0032] A technical solution in the method for preparing perovskite ink of the present invention has at least the following beneficial effects:

[0033] The preparation method of the present invention does not require expensive equipment and complicated process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, and is easy to industrialize.

[0034] According to some embodiments of the present invention, the perovskite ink preparation process is carried out in a glove box with anhydrous and oxygen-free inert gas, and the overall process is: weighing the solute - adding the solvent - stirring.

[0035] According to some embodiments of the present invention, during the preparation of the perovskite ink, the solute weighing error and the solvent addition error are less than 1%.

[0036] According to some embodiments of the present invention, during the preparation of perovskite ink, stirring is performed during the mixing of the solute and the solvent, and the stirring time is 2 to 30 hours. During the stirring process, the magnetic stirring table is heated or not heated.

[0037] The third aspect of the present invention provides a perovskite solar cell, comprising a substrate layer, a hole transport layer, an absorption layer, an electron transport layer, a functional layer and an electrode layer arranged in sequence, wherein the absorption layer is prepared from the perovskite ink of the first aspect of the present invention.

[0038] One of the technical solutions of the present invention for perovskite solar cells has at least the following beneficial effects:

[0039] Improved crystallinity and grain size: The perovskite film prepared using the perovskite ink of the present invention has higher crystallinity, larger grain size, and no pinhole defects after annealing, thereby improving the photoelectric conversion efficiency of the battery.

[0040] Higher energy conversion efficiency: Compared with the traditional DMF+DMSO solvent system, the perovskite solar cell prepared using the perovskite ink of the present invention has a higher energy conversion efficiency, thereby improving the overall performance of the cell.

[0041] Better stability: Under the same battery structure and operating environment, the perovskite solar cell prepared using the ink of the present invention exhibits higher stability than the traditional solvent system, thereby extending the service life of the battery.

[0042] Environmental protection and safety: Compared with the DMF+DMSO system, the ink system of the present invention is less toxic and significantly less harmful to human health and the environment, which is conducive to achieving environmental protection in the preparation process of perovskite batteries.

[0043] Therefore, the perovskite solar cell of the present invention not only has improved performance, but also has advantages in safety and environmental friendliness.

[0044] According to some embodiments of the present invention, the base layer includes one of a FTO base layer, an ITO base layer, and an AZO base layer.

[0045] According to some embodiments of the present invention, the substrate layer is FTO.

[0046] According to some embodiments of the present invention, the hole transport layer includes at least one of nickel oxide, phosphoric acid containing a carbazole group, poly(3-hexylthiophene-2,5-diyl), poly-3,4-ethylenedioxythiophene, 2,2",7,7"-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], copper thiocyanate, cuprous oxide, and aluminum oxide.

[0047] According to some embodiments of the present invention, the hole transport layer is nickel oxide.

[0048] According to some embodiments of the present invention, the component of the absorption layer is FA x Cs y MA (1-x-y) PbI z Br (3-z) ; Among them, x is 0.8~0.98; y is 0.02~0.2; z is 2.5~3.

[0049] According to some embodiments of the present invention, the component of the absorption layer is FA 0.9 Cs 0.1 PbI3 or FA 0.85 Cs 0.05 MA 0.1 Pb(I 0.9 Br 0.1 )3.

[0050] According to some embodiments of the present invention, the electron transport layer includes at least one of C60, PCBM, and ICBA.

[0051] According to some embodiments of the present invention, the electron transport layer is PCBM.

[0052] According to some embodiments of the present invention, the functional layer includes at least one of BCP, SnO2, ZnO, Al2O3 and LiF.

[0053] According to some embodiments of the present invention, the functional layer is BCP.

[0054] According to some embodiments of the present invention, the electrode layer is preferably made of at least one of copper, silver, gold, aluminum, or partially or entirely of a transparent conductive oxide (such as ITO, IZO, etc.).

[0055] According to some embodiments of the present invention, the electrode layer is silver.

[0056] The fourth aspect of the present invention provides a method for preparing the perovskite solar cell according to the third aspect of the present invention, comprising the following steps:

[0057] Prepare the hole transport layer on the surface of the substrate layer;

[0058] Prepare the absorption layer on the surface of the hole transport layer;

[0059] Prepare the electron transport layer on the surface of the absorption layer;

[0060] Preparing the functional layer on the surface of the electron transport layer;

[0061] The electrode layer is prepared on the surface of the functional layer to obtain the perovskite solar cell.

[0062] A technical solution in the method for preparing a perovskite solar cell according to the present invention has at least the following beneficial effects:

[0063] The method of the present invention adopts a layer-by-layer preparation process, so that each functional layer (base layer, hole transport layer, absorption layer, electron transport layer, functional layer and electrode layer) can be prepared separately. The process steps are clear and easy to control, which helps to improve the consistency and repeatability of the battery.

[0064] Furthermore, by precisely controlling the preparation process of each layer, especially in the preparation of the absorption layer and the transport layer, the carrier transport performance at the interface of each layer can be optimized, thereby improving the overall photoelectric conversion efficiency and stability of the battery.

[0065] Furthermore, the method of the present invention is compatible with a variety of preparation techniques, such as spin coating, blade coating, spray coating, etc., and can adapt to production needs of different scales and scenarios, and has good prospects for industrial application.

[0066] In addition, precise control of the multilayer structure, especially in the preparation of the electron transport layer and the functional layer, helps to reduce interface defects and internal losses of the battery, thereby improving the long-term stability of the battery.

[0067] Therefore, the preparation method of the present invention can improve the efficiency, stability and industrial feasibility of perovskite solar cells by simplifying the process flow and improving the quality of key layers.

[0068] According to some embodiments of the present invention, before preparing the hole transport layer, the substrate needs to be ultrasonically cleaned in sequence using a cleaning agent, deionized water, acetone, and ethanol, and the cleaning time is preferably 10 to 30 minutes, more preferably 20 minutes.

[0069] According to some embodiments of the present invention, the hole transport layer is preferably prepared by one of spin coating, blade coating, vacuum sputtering, and atomic layer deposition.

[0070] According to some embodiments of the present invention, the hole transport layer is preferably prepared by spin coating.

[0071] According to some embodiments of the present invention, the spin coating speed is preferably 2000-4500 rpm.

[0072] According to some embodiments of the present invention, the spin coating speed is more preferably 3000 rpm.

[0073] According to some embodiments of the present invention, the spin coating time is preferably 10 to 40 seconds.

[0074] According to some embodiments of the present invention, the spin coating time is more preferably 30 s.

[0075] According to some embodiments of the present invention, the thickness of the hole transport layer is preferably 10 to 40 nm.

[0076] According to some embodiments of the present invention, the thickness of the hole transport layer is more preferably 30 nm.

[0077] According to some embodiments of the present invention, the preparation process of the absorption layer includes: wet film coating - solvent removal - annealing treatment.

[0078] According to some embodiments of the present invention, the wet film coating adopts one or two of slit coating, spin coating, blade coating, and chemical vapor deposition.

[0079] According to some embodiments of the present invention, wet film coating is performed by slot coating.

[0080] According to some embodiments of the present invention, the coating speed of the slit coating is preferably 5 to 20 mm / s.

[0081] According to some embodiments of the present invention, the coating speed of the slit coating is more preferably 10 mm / s.

[0082] According to some embodiments of the present invention, the method for removing the solvent adopts one of the anti-solvent method, air knife blowing, and reduced pressure drying process.

[0083] According to some embodiments of the present invention, the method for removing the solvent is a reduced pressure drying process.

[0084] According to some embodiments of the present invention, the working pressure range of the reduced pressure drying process is preferably 0.2Pa to 650Pa.

[0085] According to some embodiments of the present invention, the working pressure of the reduced pressure drying process is more preferably 450Pa.

[0086] According to some embodiments of the present invention, the vacuuming time of the reduced pressure drying process is preferably 10 to 60 seconds.

[0087] According to some embodiments of the present invention, the vacuuming time of the reduced pressure drying process is more preferably 20 seconds.

[0088] According to some embodiments of the present invention, the perovskite absorption layer annealing treatment adopts one of a two-step annealing method, a one-step annealing method, and a gradient annealing method.

[0089] According to some embodiments of the present invention, the annealing treatment of the perovskite absorber layer is more preferably a one-step annealing method.

[0090] According to some embodiments of the present invention, the annealing temperature of the perovskite absorber layer annealing treatment is preferably 100-150°C.

[0091] According to some embodiments of the present invention, the annealing temperature of the perovskite absorber layer annealing treatment is more preferably 150°C.

[0092] According to some embodiments of the present invention, the annealing time of the perovskite absorber layer is preferably 10 to 60 minutes.

[0093] According to some embodiments of the present invention, the annealing time of the perovskite absorber layer is more preferably 10 minutes.

[0094] According to some embodiments of the present invention, the thickness of the perovskite absorption layer is preferably 400-650 nm.

[0095] According to some embodiments of the present invention, the thickness of the perovskite absorption layer is more preferably 550 nm.

[0096] According to some embodiments of the present invention, the electron transport layer is preferably prepared by a method selected from the group consisting of spin coating, vacuum evaporation, and chemical vapor deposition.

[0097] According to some embodiments of the present invention, the electron transport layer is preferably prepared by spin coating.

[0098] According to some embodiments of the present invention, in the method for preparing the electron transport layer, the spin coating speed is preferably 1000 to 4500 rpm.

[0099] According to some embodiments of the present invention, in the method for preparing the electron transport layer, the spin coating speed is more preferably 2000 rpm.

[0100] According to some embodiments of the present invention, in the method for preparing the electron transport layer, the spin coating time is preferably 10 to 40 seconds.

[0101] According to some embodiments of the present invention, in the method for preparing the electron transport layer, the spin coating time is more preferably 30 s.

[0102] According to some embodiments of the present invention, the thickness of the electron transport layer is preferably 10 to 40 nm.

[0103] According to some embodiments of the present invention, the thickness of the electron transport layer is more preferably 20 nm.

[0104] According to some embodiments of the present invention, the functional layer is preferably prepared by a method selected from the group consisting of spin coating, chemical vapor deposition, and physical vapor deposition.

[0105] According to some embodiments of the present invention, the method for preparing the functional layer is more preferably a vacuum evaporation method.

[0106] According to some embodiments of the present invention, in the method for preparing the functional layer, the evaporation rate is preferably

[0108] According to some embodiments of the present invention, in the method for preparing the functional layer, the evaporation rate is more preferably

[0110] According to some embodiments of the present invention, the thickness of the functional layer is preferably 5 to 10 nm.

[0111] According to some embodiments of the present invention, the thickness of the functional layer is more preferably 6 nm.

[0112] According to some embodiments of the present invention, the electrode layer is preferably prepared by physical vapor deposition.

[0113] According to some embodiments of the present invention, the preparation method of the electrode layer is more preferably vacuum evaporation.

[0114] According to some embodiments of the present invention, in the method for preparing the electrode layer, the evaporation speed is preferably

[0116] According to some embodiments of the present invention, in the method for preparing the electrode layer, the evaporation rate is preferably

[0118] According to some embodiments of the present invention, the thickness of the electrode layer is preferably 80 to 200 nm.

[0119] According to some embodiments of the present invention, the thickness of the electrode layer is more preferably 100 nm. BRIEF DESCRIPTION OF THE DRAWINGS

[0120] Figure 1 This is a microscopic morphology of the perovskite film of Example 2 of the present invention.

[0121] Figure 2 This is a physical picture of the perovskite film of Example 2 of the present invention.

[0122] Figure 3 It is a schematic structural diagram of the perovskite solar cell of the present invention.

[0123] Figure 4 This is the JV curve test result of the perovskite solar cell of the present invention.

[0124] Figure 5 This is the stability JV curve test result of the perovskite solar cell in Example 2 of the present invention. DETAILED DESCRIPTION

[0125] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0126] In the first aspect, in some embodiments of the present invention, a perovskite ink is provided, the components of which include a precursor solution A and a precursor solution B, the precursor solution A includes a solute A and a solvent A, the precursor solution B includes a solute B and a solvent B, the solute A includes at least one of methylamine halide, methylammonium halide, cesium halide and lead halide, the solvent A is 2-methoxyethanol, the solute B includes at least one of cesium halide, lead halide and methylamine halide, and the solvent B includes at least one of acetonitrile, N-methyl-2-pyrrolidone, 1,3-dimethyl-3,4,5,6-tetrahydro-2-pyrimidinone, ethanol and 1-cyclohexyl-2-pyrrolidone.

[0127] It can be understood that under the same atmosphere, the perovskite film prepared using the perovskite ink of the present invention has higher crystallinity, larger grain size after annealing, and no pinholes.

[0128] Under the same cell structure, the energy conversion efficiency of the perovskite solar cell prepared using the perovskite ink of the present invention is higher than that of the traditional DMF+DMSO solvent system.

[0129] Under the same atmosphere and battery structure, the stability of the perovskite solar cell prepared using the perovskite ink of the present invention is better than that of the traditional DMF+DMSO solvent system.

[0130] Compared with the DMF+DMSO solvent system, the solvent system of the perovskite ink of the present invention is less toxic and less harmful to the human body and the natural environment.

[0131] In combination with the first aspect, in some embodiments of the present invention, the concentration of the precursor solution A is 0.6-1.6 mol / L.

[0132] In combination with the first aspect, in some embodiments of the present invention, the concentration of the precursor solution A is any value among 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 mol / L or a range formed by any two of them.

[0133] In combination with the first aspect, in some embodiments of the present invention, the concentration of the precursor solution A is 1.0 mol / L.

[0134] In combination with the first aspect, in some embodiments of the present invention, the concentration of the precursor solution B is 0.2-1.2 mol / L.

[0135] In combination with the first aspect, in some embodiments of the present invention, the concentration of the precursor solution B is any value of 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 mol / L or a range formed by any two of them.

[0136] In combination with the first aspect, in some embodiments of the present invention, the concentration of the precursor solution B is 0.6-1.0 mol / L.

[0137] In combination with the first aspect, in some embodiments of the present invention, the volume ratio of precursor solution A and precursor solution B is calculated based on the perovskite composition and the precursor solution concentration.

[0138] In combination with the first aspect, in some embodiments of the present invention, the solute A is selected from at least one of methylamine halides, formamidine halides, cesium halides and lead halides.

[0139] In combination with the first aspect, in some embodiments of the present invention, solute A is selected from at least one of MABr, MACl, PbI2, PbBr2, and FAI.

[0140] In combination with the first aspect, in some embodiments of the present invention, solvent A is 2-methoxyethanol.

[0141] In combination with the first aspect, in some embodiments of the present invention, solute B is selected from at least one of cesium halide, lead halide and methylamine halide.

[0142] In combination with the first aspect, in some embodiments of the present invention, solute B is selected from at least one of PbI2, CsI, and MACl.

[0143] In combination with the first aspect, in some embodiments of the present invention, solvent B is selected from at least one of acetonitrile, N-methyl-2-pyrrolidone, 1,3-dimethyl-3,4,5,6-tetrahydro-2-pyrimidinone, ethanol and 1-cyclohexyl-2-pyrrolidone.

[0144] In combination with the first aspect, in some embodiments of the present invention, solvent B is N-methyl-2-pyrrolidone and / or acetonitrile.

[0145] In a second aspect, in some embodiments of the present invention, there is provided a method for preparing the perovskite ink of the first aspect of the present invention, comprising the following steps:

[0146] Dissolving solute A in solvent A to obtain precursor solution A;

[0147] Dissolving solute B in solvent B to obtain precursor solution B;

[0148] The precursor solution A and the precursor solution B are mixed to obtain the perovskite ink of the present invention.

[0149] It can be understood that the preparation method of the present invention does not require expensive equipment and complex process control, the reaction conditions are not harsh, the raw materials are easily available, the production cost is low, and it is easy to industrialize production.

[0150] In combination with the second aspect, in some embodiments of the present invention, the perovskite ink preparation process is carried out in a glove box with anhydrous and oxygen-free inert gas, and the overall process is: weighing the solute - adding the solvent - stirring.

[0151] In combination with the second aspect, in some embodiments of the present invention, during the preparation of the perovskite ink, the solute weighing error and the solvent addition amount error are less than 1%.

[0152] In combination with the second aspect, in some embodiments of the present invention, during the preparation of the perovskite ink, the solute and the solvent are stirred during the mixing process, and the stirring time is 2 to 30 hours. During the stirring process, the magnetic stirring table is heated or not heated.

[0153] In a third aspect, in some embodiments of the present invention, a perovskite solar cell is provided, comprising a substrate layer, a hole transport layer, an absorption layer, an electron transport layer, a functional layer and an electrode layer arranged in sequence, and the absorption layer is prepared from the perovskite ink of the first aspect of the present invention.

[0154] It can be understood that the perovskite film prepared using the perovskite ink of the present invention has higher crystallinity, larger grain size, and no pinhole defects after annealing, thereby improving the photoelectric conversion efficiency of the battery.

[0155] Compared with the traditional DMF+DMSO solvent system, the perovskite solar cell prepared using the perovskite ink of the present invention has higher energy conversion efficiency, thereby improving the overall performance of the battery.

[0156] Under the same cell structure and operating environment, the perovskite solar cell prepared using the ink of the present invention exhibits higher stability than the traditional solvent system, thereby extending the service life of the cell.

[0157] Compared with the DMF+DMSO system, the ink system of the present invention is less toxic and significantly less harmful to human health and the environment, which is conducive to achieving an environmentally friendly perovskite battery preparation process.

[0158] Therefore, the perovskite solar cell of the present invention not only has improved performance, but also has advantages in safety and environmental friendliness.

[0159] In combination with the third aspect, in some embodiments of the present invention, the base layer includes one of a FTO base layer, an ITO base layer, and an AZO base layer.

[0160] In combination with the third aspect, in some embodiments of the present invention, the base layer is FTO.

[0161] In combination with the third aspect, in some embodiments of the present invention, the hole transport layer includes at least one of nickel oxide, phosphoric acid containing a carbazole group, poly(3-hexylthiophene-2,5-diyl), poly-3,4-ethylenedioxythiophene, 2,2",7,7"-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], copper thiocyanate, cuprous oxide, and aluminum oxide.

[0162] In combination with the third aspect, in some embodiments of the present invention, the hole transport layer is nickel oxide.

[0163] In combination with the third aspect, in some embodiments of the present invention, the component of the absorption layer is FA x Cs y MA (1-x-y) PbI z Br (3-z) ; Among them, x is 0.8~0.98; y is 0.02~0.2; z is 2.5~3.

[0164] In combination with the third aspect, in some embodiments of the present invention, the component of the absorption layer is FA 0.9Cs 0.1 PbI3、FA 0.85 Cs 0.05 MA 0.1 Pb(I 0.9 Br 0.1 )3.

[0165] In combination with the third aspect, in some embodiments of the present invention, the electron transport layer includes at least one of C60, PCBM, and ICBA.

[0166] In combination with the third aspect, in some embodiments of the present invention, the electron transport layer is PCBM.

[0167] In combination with the third aspect, in some embodiments of the present invention, the functional layer includes at least one of BCP, SnO2, ZnO, Al2O3 and LiF.

[0168] In combination with the third aspect, in some embodiments of the present invention, the functional layer is BCP.

[0169] In combination with the third aspect, in some embodiments of the present invention, the electrode layer includes at least one of copper, silver, gold, aluminum, and partially or entirely transparent conductive oxides (such as ITO, IZO, etc.).

[0170] In combination with the third aspect, in some embodiments of the present invention, the electrode layer is silver.

[0171] In a fourth aspect, in some embodiments of the present invention, there is provided a method for preparing the perovskite solar cell according to the third aspect of the present invention, comprising the following steps:

[0172] preparing a hole transport layer on the surface of the substrate layer;

[0173] preparing an absorption layer on the surface of the hole transport layer;

[0174] preparing an electron transport layer on the surface of the absorption layer;

[0175] preparing a functional layer on the surface of the electron transport layer;

[0176] An electrode layer is prepared on the surface of the functional layer to obtain the perovskite solar cell of the present invention.

[0177] The method of the present invention adopts a layer-by-layer preparation process, so that each functional layer (base layer, hole transport layer, absorption layer, electron transport layer, functional layer and electrode layer) can be prepared separately. The process steps are clear and easy to control, which helps to improve the consistency and repeatability of the battery.

[0178] Furthermore, by precisely controlling the preparation process of each layer, especially in the preparation of the absorption layer and the transport layer, the carrier transport performance at the interface of each layer can be optimized, thereby improving the overall photoelectric conversion efficiency and stability of the battery.

[0179] Furthermore, the method of the present invention is compatible with a variety of preparation techniques, such as spin coating, blade coating, spray coating, etc., and can adapt to production needs of different scales and scenarios, and has good prospects for industrial application.

[0180] In addition, precise control of the multilayer structure, especially in the preparation of the electron transport layer and the functional layer, helps to reduce interface defects and internal losses of the battery, thereby improving the long-term stability of the battery.

[0181] Therefore, the preparation method of the present invention can improve the efficiency, stability and industrial feasibility of perovskite solar cells by simplifying the process flow and improving the quality of key layers.

[0182] In combination with the fourth aspect, in some embodiments of the present invention, before preparing the hole transport layer, the substrate needs to be ultrasonically cleaned in sequence using a detergent, deionized water, acetone, and ethanol, and the cleaning time is preferably 10 to 30 minutes, more preferably 20 minutes.

[0183] In combination with the fourth aspect, in some embodiments of the present invention, the hole transport layer is preferably prepared by one of spin coating, scraper coating, vacuum sputtering, and atomic layer deposition.

[0184] In combination with the fourth aspect, in some embodiments of the present invention, the hole transport layer is more preferably prepared by spin coating.

[0185] In combination with the fourth aspect, in some embodiments of the present invention, the spin coating rotation speed is preferably 2000-4500 rpm.

[0186] In combination with the fourth aspect, in some embodiments of the present invention, the spin coating speed is more preferably 3000 rpm.

[0187] In combination with the fourth aspect, in some embodiments of the present invention, the spin coating time is preferably 10 to 40 seconds.

[0188] In combination with the fourth aspect, in some embodiments of the present invention, the spin coating time is more preferably 30 s.

[0189] In combination with the fourth aspect, in some embodiments of the present invention, the thickness of the hole transport layer is preferably 10 to 40 nm.

[0190] In combination with the fourth aspect, in some embodiments of the present invention, the thickness of the hole transport layer is more preferably 30 nm.

[0191] In combination with the fourth aspect, in some embodiments of the present invention, the preparation process of the absorption layer includes: wet film coating—removal of solvent—annealing treatment.

[0192] In combination with the fourth aspect, in some embodiments of the present invention, wet film coating includes one or two of slit coating, spin coating, blade coating, and chemical vapor deposition.

[0193] In conjunction with the fourth aspect, in some embodiments of the present invention, wet film coating includes slot coating.

[0194] In combination with the fourth aspect, in some embodiments of the present invention, the coating speed of the slit coating is preferably 5 to 20 mm / s.

[0195] In combination with the fourth aspect, in some embodiments of the present invention, the coating speed of the slit coating is more preferably 10 mm / s.

[0196] In combination with the fourth aspect, in some embodiments of the present invention, the method for removing the solvent adopts one of the anti-solvent method, air knife blowing, and reduced pressure drying process.

[0197] In combination with the fourth aspect, in some embodiments of the present invention, the method for removing the solvent is a reduced pressure drying process.

[0198] In combination with the fourth aspect, in some embodiments of the present invention, the working pressure range of the reduced pressure drying process is preferably 0.2Pa to 650Pa.

[0199] In combination with the fourth aspect, in some embodiments of the present invention, the working pressure of the reduced pressure drying process is more preferably 450Pa.

[0200] In combination with the fourth aspect, in some embodiments of the present invention, the vacuuming time of the reduced pressure drying process is preferably 10 to 60 seconds.

[0201] In combination with the fourth aspect, in some embodiments of the present invention, the vacuuming time of the reduced pressure drying process is more preferably 20 seconds.

[0202] In combination with the fourth aspect, in some embodiments of the present invention, the annealing treatment of the perovskite absorption layer adopts one of a two-step annealing method, a one-step annealing method, and a gradient annealing method.

[0203] In combination with the fourth aspect, in some embodiments of the present invention, the annealing treatment of the perovskite absorber layer is more preferably a one-step annealing method.

[0204] In combination with the fourth aspect, in some embodiments of the present invention, the annealing temperature of the perovskite absorber layer annealing treatment is preferably 100-150°C.

[0205] In combination with the fourth aspect, in some embodiments of the present invention, the annealing temperature of the perovskite absorber layer annealing treatment is more preferably 150°C.

[0206] In combination with the fourth aspect, in some embodiments of the present invention, the annealing time of the perovskite absorption layer is preferably 10 to 60 minutes.

[0207] In combination with the fourth aspect, in some embodiments of the present invention, the annealing time of the perovskite absorption layer is more preferably 10 minutes.

[0208] In combination with the fourth aspect, in some embodiments of the present invention, the thickness of the perovskite absorption layer is preferably 400-650 nm.

[0209] In combination with the fourth aspect, in some embodiments of the present invention, the thickness of the perovskite absorption layer is more preferably 550 nm.

[0210] In combination with the fourth aspect, in some embodiments of the present invention, the preparation method of the electron transport layer is preferably one of spin coating, vacuum evaporation, and chemical vapor deposition.

[0211] In combination with the fourth aspect, in some embodiments of the present invention, the method for preparing the electron transport layer is more preferably spin coating.

[0212] In combination with the fourth aspect, in some embodiments of the present invention, in the method for preparing the electron transport layer, the spin coating speed is preferably 1000 to 4500 rpm.

[0213] In combination with the fourth aspect, in some embodiments of the present invention, in the method for preparing the electron transport layer, the spin coating speed is more preferably 2000 rpm.

[0214] In combination with the fourth aspect, in some embodiments of the present invention, in the method for preparing the electron transport layer, the spin coating time is preferably 10 to 40 seconds.

[0215] In combination with the fourth aspect, in some embodiments of the present invention, in the method for preparing the electron transport layer, the spin coating time is more preferably 30 s.

[0216] In combination with the fourth aspect, in some embodiments of the present invention, the thickness of the electron transport layer is preferably 10 to 40 nm.

[0217] In combination with the fourth aspect, in some embodiments of the present invention, the thickness of the electron transport layer is more preferably 20 nm.

[0218] In combination with the fourth aspect, in some embodiments of the present invention, the preparation method of the functional layer is preferably one of spin coating, chemical vapor deposition, and physical vapor deposition.

[0219] In combination with the fourth aspect, in some embodiments of the present invention, the method for preparing the functional layer is more preferably a vacuum evaporation method.

[0220] In conjunction with the fourth aspect, in some embodiments of the present invention, in the method for preparing the functional layer, the evaporation speed is preferably

[0222] In combination with the fourth aspect, in some embodiments of the present invention, in the method for preparing the functional layer, the evaporation rate is preferably

[0223] In conjunction with the fourth aspect, in some embodiments of the present invention, the thickness of the functional layer is preferably 5 to 10 nm.

[0224] In combination with the fourth aspect, in some embodiments of the present invention, the thickness of the functional layer is more preferably 6 nm.

[0225] In combination with the fourth aspect, in some embodiments of the present invention, the electrode layer is preferably copper, silver, gold, aluminum, or partially or entirely transparent conductive oxide (such as ITO, IZO, etc.).

[0226] In combination with the fourth aspect, in some embodiments of the present invention, the electrode layer is more preferably silver.

[0227] In combination with the fourth aspect, in some embodiments of the present invention, the electrode layer is preferably prepared by physical vapor deposition.

[0228] In combination with the fourth aspect, in some embodiments of the present invention, the preparation method of the electrode layer is more preferably vacuum evaporation.

[0229] In conjunction with the fourth aspect, in some embodiments of the present invention, in the method for preparing the electrode layer, the evaporation speed is preferably

[0231] In conjunction with the fourth aspect, in some embodiments of the present invention, in the method for preparing the electrode layer, the evaporation speed is preferably

[0232] In combination with the fourth aspect, in some embodiments of the present invention, the thickness of the electrode layer is preferably 80 to 200 nm.

[0233] In combination with the fourth aspect, in some embodiments of the present invention, the thickness of the electrode layer is more preferably 100 nm.

[0234] In some embodiments of the present invention, the present invention uses 2-methoxyethanol and N-methylpyrrolidone as a mixed solvent system to prepare perovskite ink. During the crystallization and film formation process of the perovskite absorption layer, 2-methoxyethanol can be quickly removed due to its relatively low boiling point. The introduction of the strong coordinating cosolvent N-methylpyrrolidone is conducive to reducing the overall viscosity of the solvent system, and at the same time, a stable intermediate phase can be formed, and a high-quality perovskite film can be obtained after annealing.

[0235] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0236] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0237] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0238] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.

[0239] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0240] Example 1

[0241] In this embodiment, a perovskite ink is first prepared, and the preparation process is as follows:

[0242] Lead iodide, iodoformamidine, and methylamine chloride were weighed in a molar ratio of 10:10:3 in an anhydrous and oxygen-free glove box;

[0243] Add 2-methoxyethanol solvent to prepare a precursor solution A with a concentration of 1.0 mol / L;

[0244] Then, lead iodide and cesium iodide in a molar ratio of 1:1 were weighed and added to N-methyl-2-pyrrolidone solvent to prepare a precursor solution B with a concentration of 0.6 mol / L;

[0245] The precursor solutions A and B, which were stirred until clear, were mixed in a volume ratio of 5.4:1.

[0246] Then prepare the perovskite solar cell, the specific process is:

[0247] An FTO conductive glass substrate with a length, width and height of 5 cm×5 cm×0.32 cm was used as the substrate, and was ultrasonically cleaned in sequence with a cleaning agent, deionized water, acetone and ethanol before use.

[0248] NiO was prepared on FTO substrate by spin coating x For the hole transport layer, 0.5 mg of nickel oxide powder was weighed in a water-free and oxygen-free glove box, 1 ml of deionized water was added, and the mixture was spin-coated on the substrate at a speed of 3000 rpm after ultrasonic oscillation for 10 minutes, and then annealed at 150° C. for 10 minutes to obtain the hole transport layer.

[0249] A perovskite absorption layer was prepared on the surface of the hole transport layer, and the perovskite ink was coated on the surface of the hole transport layer through a slit to prepare a perovskite film at a coating speed of 10 mm / s. The film was evacuated in a 450 Pa vacuum box for 20 seconds, and then annealed at 150°C for 10 minutes to obtain the perovskite absorption layer.

[0250] An electron transport layer was prepared on the surface of the perovskite absorption layer. A PCBM solution with a concentration of 20 mg / ml was prepared in an anhydrous and oxygen-free glove box, and was spin-coated on the surface of the perovskite absorption layer at a rotation speed of 2000 rpm. The electron transport layer was obtained after annealing at 100° C. for 5 minutes.

[0251] The functional layer was prepared on the surface of the electron transport layer at 5×10 -4 Pa high vacuum environment, BCP was evaporated onto the surface of the electron transport layer, and the evaporation rate Get the functional layer.

[0252] The electrode layer was prepared on the surface of the functional layer at 5×10 -4 Pa high vacuum environment, metal Ag is evaporated onto the surface of the functional layer, and the evaporation rate Get perovskite solar cells, such as Figure 3 shown.

[0253] Example 2

[0254] In this embodiment, a perovskite ink is first prepared, and the preparation process is as follows:

[0255] Lead iodide, iodoformamidine, and methylamine chloride were weighed in a molar ratio of 10:10:3 in an anhydrous and oxygen-free glove box, and added to 2-methoxyethanol solvent to prepare a precursor solution A with a concentration of 1.0 mol / L;

[0256] Then, lead iodide and cesium iodide in a molar ratio of 1:1 were weighed and added to N-methyl-2-pyrrolidone solvent to prepare a precursor solution B with a concentration of 0.8 mol / L;

[0257] The precursor solutions A and B, which were stirred until clear, were mixed in a volume ratio of 7.2:1.

[0258] Then prepare the perovskite solar cell, the specific process is:

[0259] An FTO conductive glass substrate with a length, width and height of 5 cm×5 cm×0.32 cm was used as the substrate, and was ultrasonically cleaned in sequence with a cleaning agent, deionized water, acetone and ethanol before use.

[0260] NiO was prepared on FTO substrate by spin coating x For the hole transport layer, 0.5 mg of nickel oxide powder was weighed in a water-free and oxygen-free glove box, 1 ml of deionized water was added, and the mixture was spin-coated on the substrate at a speed of 3000 rpm after ultrasonic oscillation for 10 minutes, and then annealed at 150° C. for 10 minutes to obtain the hole transport layer.

[0261] The perovskite absorption layer was prepared on the surface of the hole transport layer. The perovskite ink was coated on the surface of the hole transport layer through a slit to prepare a perovskite film. The coating speed was 10 mm / s. The film was evacuated in a 450 Pa vacuum box for 20 seconds and then annealed at 150°C for 10 minutes to obtain the perovskite absorption layer. The microscopic morphology is shown in FIG. Figure 1 As shown, the actual Figure 2 As shown, it can be seen that the film has no pinholes, is uniform and dense, and has good crystal quality.

[0262] An electron transport layer was prepared on the surface of the perovskite absorption layer. A PCBM solution with a concentration of 20 mg / ml was prepared in an anhydrous and oxygen-free glove box, and was spin-coated on the surface of the perovskite absorption layer at a rotation speed of 2000 rpm. The electron transport layer was obtained after annealing at 100° C. for 5 minutes.

[0263] The functional layer was prepared on the surface of the electron transport layer at 5×10 -4 Pa high vacuum environment, BCP was evaporated onto the surface of the electron transport layer, and the evaporation rate Get the functional layer.

[0264] The electrode layer was prepared on the surface of the functional layer at 5×10 -4 Pa high vacuum environment, metal Ag is evaporated onto the surface of the functional layer, and the evaporation rate Obtained perovskite solar cell.

[0265] Example 3

[0266] In this embodiment, a perovskite ink is first prepared, and the preparation process is as follows:

[0267] Lead iodide, iodoformamidine, and methylamine chloride were weighed in a molar ratio of 10:10:3 in an anhydrous and oxygen-free glove box, and added to 2-methoxyethanol solvent to prepare a precursor solution A with a concentration of 1.0 mol / L;

[0268] Then, lead iodide and cesium iodide in a molar ratio of 1:1 were weighed and added to N-methyl-2-pyrrolidone solvent to prepare a precursor solution B with a concentration of 1.mol / L;

[0269] The precursor solutions A and B, which were stirred until clear, were mixed in a volume ratio of 9:1.

[0270] Then prepare the perovskite solar cell, the specific process is:

[0271] An FTO conductive glass substrate with a length, width and height of 5 cm×5 cm×0.32 cm was used as the substrate, and was ultrasonically cleaned in sequence with a cleaning agent, deionized water, acetone and ethanol before use.

[0272] NiO was prepared on FTO substrate by spin coating x For the hole transport layer, 0.5 mg of nickel oxide powder was weighed in a water-free and oxygen-free glove box, 1 ml of deionized water was added, and the mixture was spin-coated on the substrate at a speed of 3000 rpm after ultrasonic oscillation for 10 minutes, and then annealed at 150° C. for 10 minutes to obtain the hole transport layer.

[0273] A perovskite absorption layer was prepared on the surface of the hole transport layer. The perovskite ink was coated on the surface of the hole transport layer through a slit to prepare the perovskite layer. The coating speed was 10 mm / s. The vacuum was drawn in a 450 Pa vacuum air box for 20 seconds, and then annealed at 150°C for 10 minutes to obtain the perovskite absorption layer.

[0274] An electron transport layer was prepared on the surface of the perovskite absorption layer. A PCBM solution with a concentration of 20 mg / ml was prepared in an anhydrous and oxygen-free glove box, and was spin-coated on the surface of the perovskite absorption layer at a rotation speed of 2000 rpm. The electron transport layer was obtained after annealing at 100° C. for 5 minutes.

[0275] The functional layer was prepared on the surface of the electron transport layer at 5×10 -4 Pa high vacuum environment, BCP was evaporated onto the surface of the electron transport layer, and the evaporation rate Get the functional layer.

[0276] The electrode layer was prepared on the surface of the functional layer at 5×10 -4 Pa high vacuum environment, metal Ag is evaporated onto the surface of the functional layer, and the evaporation rate Obtained perovskite solar cell.

[0277] It should be noted that, due to the limited solubility of cesium halide in 2-methoxyethanol, cesium halide can only be dissolved in solvent B. In Examples 1-3, the perovskite components are all FA 0.9 Cs 0.1PbI3, the methylamine halide is methylamine chloride, which as an additive does not enter the perovskite component and can be dissolved in solute A or solute B. There is no obvious difference in the final experimental effect. For details, see the following Example 4 and Table 1.

[0278] The range of solvents and solutes defined in the embodiments of the present invention is that solute A is selected from at least one of methylamine halides, formamidine halides, cesium halides, and lead halides. Solute B is selected from at least one of cesium halides, lead halides, and methylamine halides. Solvent A is 2-methoxyethanol, and solvent B is selected from at least one of acetonitrile, N-methyl-2-pyrrolidone, 1,3-dimethyl-3,4,5,6-tetrahydro-2-pyrimidone, ethanol, and 1-cyclohexyl-2-pyrrolidone.

[0279] In the present invention, different solutes can be selected to obtain different perovskite components, and different perovskite components have different final performances under the same solvent. Different solutes can be selected in various combinations to obtain different perovskite components, that is, different halides AX (A = methylamine MA, cesium Cs, formamidine FA, lead Pb; X = Cl, Br, I) can be used for combination. In Examples 1-3, the perovskite components are all FA 0.9 Cs 0.1 PbI3, composed of solute A (FAI + PbI2 + MACI) and solute B (CsI + PbI2). In addition, we can also make other combinations, such as selecting solute A (FAI + PbI2 + MACI) and solute B (CsI + PbI2 + CsBr + PbBr2) to form FA x Cs y PbI z Br (3-z) Perovskite components; solute A (FAI+PbI2+MACI+MABr) and solute B (CsI+PbI2+CsBr+PbBr2) are selected to form FA x Cs y MA (1-x-y) PbI z Br (3-z) Perovskite components, etc., see the following Example 5 and Table 1 for details. In fact, FA x MA y PbI z Br (3-z) The precursor solution of the FAPbI3 component can be prepared by directly mixing the solute and the solvent, but the purpose of the present invention is to provide a feasible solution for the industrial production of large-area perovskite films, so the relatively poor stability of FA x MA y PbI z Br (3-z) FAPbI3, which is prone to phase transition (α-δ), is not an ideal perovskite component.

[0280] In Examples 1-3, solvent A is 2-methoxyethanol, and solvent B is N-methyl-2-pyrrolidone. Solvent B may also be composed of any one or more of acetonitrile, N-methyl-2-pyrrolidone, 1,3-dimethyl-3,4,5,6-tetrahydro-2-pyrimidone, ethanol, and 1-cyclohexyl-2-pyrrolidone, as shown in the following Example 6 and Table 1 for details.

[0281] Example 4

[0282] In this embodiment, a perovskite ink is first prepared, and the preparation process is as follows:

[0283] Lead iodide and iodoformamidine were weighed in a molar ratio of 1:1 in an anhydrous and oxygen-free glove box, and added to 2-methoxyethanol solvent to prepare a precursor solution A with a concentration of 1.0 mol / L;

[0284] Then, lead iodide, cesium iodide and methylamine chloride in a molar ratio of 10:10:3 were weighed and added to N-methyl-2-pyrrolidone solvent to prepare a precursor solution B with a concentration of 0.8 mol / L;

[0285] The precursor solutions A and B, which were stirred until clear, were mixed in a volume ratio of 7.2:1.

[0286] Then prepare the perovskite solar cell, the specific process is:

[0287] An FTO conductive glass substrate with a length, width and height of 5 cm×5 cm×0.32 cm was used as the substrate, and was ultrasonically cleaned in sequence with a cleaning agent, deionized water, acetone and ethanol before use.

[0288] NiO was prepared on FTO substrate by spin coating x For the hole transport layer, 0.5 mg of nickel oxide powder was weighed in a water-free and oxygen-free glove box, 1 ml of deionized water was added, and the mixture was spin-coated on the substrate at a speed of 3000 rpm after ultrasonic oscillation for 10 minutes, and then annealed at 150° C. for 10 minutes to obtain the hole transport layer.

[0289] A perovskite absorption layer was prepared on the surface of the hole transport layer. The perovskite ink was coated on the surface of the hole transport layer through a slit to prepare the perovskite layer. The coating speed was 10 mm / s. The vacuum was drawn in a 450 Pa vacuum air box for 20 seconds, and then annealed at 150°C for 10 minutes to obtain the perovskite absorption layer.

[0290] An electron transport layer was prepared on the surface of the perovskite absorption layer. A PCBM solution with a concentration of 20 mg / ml was prepared in an anhydrous and oxygen-free glove box, and was spin-coated on the surface of the perovskite absorption layer at a rotation speed of 2000 rpm. The electron transport layer was obtained after annealing at 100° C. for 5 minutes.

[0291] The functional layer was prepared on the surface of the electron transport layer at 5×10-4 Pa high vacuum environment, BCP was evaporated onto the surface of the electron transport layer, and the evaporation rate Get the functional layer.

[0292] The electrode layer was prepared on the surface of the functional layer at 5×10 -4 Pa high vacuum environment, metal Ag is evaporated onto the surface of the functional layer, and the evaporation rate Obtained perovskite solar cell.

[0293] Example 5

[0294] In this embodiment, a perovskite ink is first prepared, and the preparation process is as follows:

[0295] In an anhydrous and oxygen-free glove box, lead iodide, iodoformamidine, methylammonium chloride, methylammonium bromide, and lead bromide were weighed in a molar ratio of 9:9:3:1:1, and added to 2-methoxyethanol solvent to prepare a precursor solution A with a concentration of 1.0 mol / L;

[0296] Then, lead iodide and cesium iodide in a molar ratio of 1:1 were weighed and added to N-methyl-2-pyrrolidone solvent to prepare a precursor solution B with a concentration of 0.8 mol / L;

[0297] The precursor solutions A and B, which were stirred until clear, were mixed in a volume ratio of 15.2:1.

[0298] Then prepare the perovskite solar cell, the specific process is:

[0299] An FTO conductive glass substrate with a length, width and height of 5 cm×5 cm×0.32 cm was used as the substrate, and was ultrasonically cleaned in sequence with a cleaning agent, deionized water, acetone and ethanol before use.

[0300] NiO was prepared on FTO substrate by spin coating x For the hole transport layer, 0.5 mg of nickel oxide powder was weighed in a water-free and oxygen-free glove box, 1 ml of deionized water was added, and the mixture was spin-coated on the substrate at a speed of 3000 rpm after ultrasonic oscillation for 10 minutes, and then annealed at 150° C. for 10 minutes to obtain the hole transport layer.

[0301] A perovskite absorption layer was prepared on the surface of the hole transport layer. The perovskite ink was coated on the surface of the hole transport layer through a slit to prepare the perovskite layer. The coating speed was 10 mm / s. The vacuum was drawn in a 450 Pa vacuum air box for 20 seconds, and then annealed at 150°C for 10 minutes to obtain the perovskite absorption layer.

[0302] An electron transport layer was prepared on the surface of the perovskite absorption layer. A PCBM solution with a concentration of 20 mg / ml was prepared in an anhydrous and oxygen-free glove box, and was spin-coated on the surface of the perovskite absorption layer at a rotation speed of 2000 rpm. The electron transport layer was obtained after annealing at 100° C. for 5 minutes.

[0303] The functional layer was prepared on the surface of the electron transport layer at 5×10 -4 Pa high vacuum environment, BCP was evaporated onto the surface of the electron transport layer, and the evaporation rate Get the functional layer.

[0304] The electrode layer was prepared on the surface of the functional layer at 5×10 -4 Pa high vacuum environment, metal Ag is evaporated onto the surface of the functional layer, and the evaporation rate Obtained perovskite solar cell.

[0305] Example 6

[0306] In this embodiment, a perovskite ink is first prepared, and the preparation process is as follows:

[0307] Lead iodide, iodoformamidine, and methylamine chloride were weighed in a molar ratio of 10:10:3 in an anhydrous and oxygen-free glove box, and added to 2-methoxyethanol solvent to prepare a precursor solution A with a concentration of 1.0 mol / L;

[0308] Then, lead iodide and cesium iodide in a molar ratio of 1:1 were weighed, and added to a mixed solvent of N-methyl-2-pyrrolidone and acetonitrile in a volume ratio of 4:1 to prepare a precursor solution B with a concentration of 0.8 mol / L;

[0309] The precursor solutions A and B, which were stirred until clear, were mixed in a volume ratio of 7.2:1.

[0310] Then prepare the perovskite solar cell, the specific process is:

[0311] An FTO conductive glass substrate with a length, width and height of 5 cm×5 cm×0.32 cm was used as the substrate, and was ultrasonically cleaned in sequence with a cleaning agent, deionized water, acetone and ethanol before use.

[0312] NiO was prepared on FTO substrate by spin coating x For the hole transport layer, 0.5 mg of nickel oxide powder was weighed in a water-free and oxygen-free glove box, 1 ml of deionized water was added, and the mixture was spin-coated on the substrate at a speed of 3000 rpm after ultrasonic oscillation for 10 minutes, and then annealed at 150° C. for 10 minutes to obtain the hole transport layer.

[0313] A perovskite absorption layer was prepared on the surface of the hole transport layer, and a perovskite cell was slit coated on the surface of the hole transport layer to prepare the perovskite layer at a coating speed of 10 mm / s. The perovskite layer was vacuumed in a 450 Pa vacuum air box for 20 seconds, and then annealed at 150°C for 10 minutes to obtain the perovskite absorption layer.

[0314] An electron transport layer was prepared on the surface of the perovskite absorption layer. A PCBM solution with a concentration of 20 mg / ml was prepared in an anhydrous and oxygen-free glove box, and was spin-coated on the surface of the perovskite absorption layer at a rotation speed of 2000 rpm. The electron transport layer was obtained after annealing at 100° C. for 5 minutes.

[0315] The functional layer was prepared on the surface of the electron transport layer at 5×10 -4 Pa high vacuum environment, BCP was evaporated onto the surface of the electron transport layer, and the evaporation rate Get the functional layer.

[0316] The electrode layer was prepared on the surface of the functional layer at 5×10 -4 Pa high vacuum environment, metal Ag is evaporated onto the surface of the functional layer, and the evaporation rate Obtained perovskite solar cell.

[0317] The difference between Example 4 and Example 2 lies in the preparation of the perovskite absorption layer. In Example 2, methylamine chloride is used as solute A, and in Example 4, methylamine chloride is used as solute B.

[0318] The difference between Example 5 and Example 2 lies in the preparation of the perovskite absorption layer. In Example 2, the perovskite component is FA 0.9 Cs 0.1 PbI3, the perovskite component in Example 5 is FA 0.85 Cs 0.05 MA 0.1 Pb(I 0.9 Br 0.1 )3.

[0319] The difference between Example 6 and Example 2 lies in the preparation of the perovskite absorption layer. In Example 2, solvent B is N-methyl-2-pyrrolidone, while in Example 6, solvent B is N-methyl-2-pyrrolidone and acetonitrile in a volume ratio of 4:1.

[0320] Comparative Example 1

[0321] In this comparative example, a perovskite ink is first prepared, and the preparation process is as follows:

[0322] In an anhydrous and oxygen-free glove box, lead iodide, iodomethane, cesium iodide, and methylamine chloride were weighed in a molar ratio of 10:9:1:3, added to a mixed solvent of DMF:DMSO=8:1 to prepare a precursor solution with a concentration of 0.8 mol / L, and stirred until clear for use.

[0323] Then prepare the perovskite solar cell, the specific process is:

[0324] An FTO conductive glass substrate with a length, width and height of 5 cm×5 cm×0.32 cm was used as the substrate, and was ultrasonically cleaned in sequence with a cleaning agent, deionized water, acetone and ethanol before use.

[0325] NiO was prepared on FTO substrate by spin coating x For the hole transport layer, 0.5 mg of nickel oxide powder was weighed in a water-free and oxygen-free glove box, 1 ml of deionized water was added, and the mixture was spin-coated on the substrate at a speed of 3000 rpm after ultrasonic oscillation for 10 minutes, and then annealed at 150° C. for 10 minutes to obtain the hole transport layer.

[0326] A perovskite absorption layer was prepared on the surface of the hole transport layer. Lead iodide, iodomethane, cesium iodide, and methylamine chloride were weighed in a molar ratio of 10:9:1:3 in an anhydrous and oxygen-free glove box, and a precursor solution with a concentration of 0.8 mol / L was prepared in a mixed solvent of DMF:DMSO=8:1. The solution was stirred until clear for use. A perovskite layer was prepared on the surface of the hole transport layer 2 by slit coating at a coating speed of 10 mm / s at 2×10 -1 The perovskite absorber layer was obtained by evacuating the sample in a vacuum box at 370 Pa for 50 s and then annealing at 150 °C for 10 min.

[0327] An electron transport layer was prepared on the surface of the perovskite absorption layer. A PCBM solution with a concentration of 20 mg / ml was prepared in an anhydrous and oxygen-free glove box, and was spin-coated on the surface of the perovskite absorption layer at a rotation speed of 2000 rpm. The electron transport layer was obtained after annealing at 100 degrees Celsius for 4 minutes.

[0328] The functional layer was prepared on the surface of the electron transport layer at 5×10 -4 Pa high vacuum environment, BCP was evaporated onto the surface of the electron transport layer, and the evaporation rate Get the functional layer.

[0329] The electrode layer was prepared on the surface of the functional layer at 5×10 -4 Pa high vacuum environment, metal Ag is evaporated onto the surface of the functional layer, and the evaporation rate Obtained perovskite solar cell.

[0330] Battery performance test

[0331] The solar simulator light source intensity was calibrated to 1 sun using a silicon reference cell calibrated by NREL, with an irradiance spectrum of AM 1.5G and a light intensity of 1000 W / m 2 , the solar cell temperature is tested at 25℃.

[0332] The results show that compared with the comparative example 1 using the traditional DMF+DMSO as the solvent system, the conversion efficiency of Examples 1, 2, 4, 5 and 6 is improved. When the concentration of the precursor solution B is 0.8 mol / L, the short-circuit current density and the open-circuit voltage increase, and the highest conversion efficiency is obtained. Figure 4Table 1. After placing the implementation case 2 in the air atmosphere for a period of time, the high efficiency is retained, see Figure 5 shown.

[0333] Table 1 is a comparison table of JV parameters of perovskite solar cells in various implementation cases of the present invention

[0334]

[0335] It should also be noted that if the solvent system is a main solvent CAN and a low volatility coordination solvent (DMSO, NMP, 4-TBP, etc.), since its coordination solvent is selected from a variety of dimethyl sulfoxide, N-methylpyrrolidone, and 4-tert-butylpyridine, it will cause a variety of coordination solvents to form a variety of intermediate phases with the perovskite precursor during the perovskite nucleation process, and there is competition and synergy between the multiple intermediate phases, thereby extending the time window for crystallization. In the present invention, the nucleation and crystallization process of the perovskite film is mainly achieved by adjusting the solvent ratio, solvent type, working pressure and vacuum duration in the reduced pressure drying process, and perovskite components in the perovskite ink. Specifically, the present invention selects solvents with low toxicity or low environmental pollution. Secondly, the most effective strategy for controlling the nucleation and growth of perovskite crystals is to adjust the coordination interaction between the solvent and the precursor in the precursor solution, that is, the coordination between the specific functional groups of the solvent and the perovskite precursor greatly affects the nucleation, crystal growth and morphology of the perovskite film. Gutmann defined the donor number (DN) to define the coordination ability of the solvent with the solute. The higher the DN, the stronger the ability of the solvent to coordinate with the electron acceptor. For the perovskite precursor solution, the solvent with high DN tends to coordinate with the electron acceptor Pb 2+ The formation of a stronger coordination compound, while the low DN solvent has a strong 2+The affinity of the perovskite film is weak. In this case, the high DN solvent will evaporate more slowly during the annealing process of the perovskite film, thereby hindering the growth of the perovskite crystal. The low DN solvent evaporates faster during the annealing process of the perovskite film, accelerating the nucleation of the perovskite crystal. In the present invention, 2-methoxyethanol is a low DN solvent with a high vapor pressure, is volatile, and has the potential for rapid crystallization (strong desolvation effect). However, the rapid volatilization of the solvent will lead to excessive nucleation and growth of the perovskite, and the quality of the prepared perovskite film is poor. In order to slow down the nucleation rate, a high DN solvent is introduced. Taking N-methyl-2-pyrrolidone (NMP) as an example, NMP has a strong coordination ability with the Lewis acid Pb(II) halide in the solute as a Lewis base to form an NMP·PbI2 intermediate phase, which can delay the crystallization and grain growth of the perovskite, and is conducive to obtaining a high-quality film. At the same time, the addition of NMP can reduce the viscosity of 2-methoxyethanol, which is conducive to improving the uniformity of the film. During the experiment, in order to obtain a good quality perovskite film and reduce surface defects such as ribbed effect and holes, another low DN solvent is introduced into the perovskite ink as a co-solvent to adjust the rheological properties of the perovskite ink. Therefore, in the present invention, the second solvent can be selected from at least one of acetonitrile, N-methyl-2-pyrrolidone, 1,3-dimethyl-3,4,5,6-tetrahydro-2-pyrimidone, ethanol, and 1-cyclohexyl-2-pyrrolidone.

[0336] Regarding the crystallization conditions, a certain amount of methylamine chloride can be additionally introduced into the solute as an additive to improve the perovskite grain size and film roughness. Therefore, in some embodiments of the present invention, 30% molar proportion of methylamine chloride is added to the solute. Secondly, the perovskite wet film in the present invention removes the solvent using a reduced pressure drying process. By adjusting the type of solvent B in the perovskite ink, the volume ratio of solvent A to solvent B, and the vacuum working pressure and duration, the volatilization rate of the solvent in the perovskite wet film can be changed, thereby affecting the perovskite film crystallization nucleation process. Finally, under the same conditions of reduced pressure drying process and solvent, changing the perovskite component will affect the perovskite crystal ABX3 (A=FA + 、MA + , Cs + etc.; B=Pb 2+ Sn 2+ etc.; C=Cl - Br - ,I - The unit cell size of the nanostructured carbon nanotubes (such as carbon nanotubes) affects the crystallization nucleation process.

[0337] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A perovskite ink, characterized in that: The components include precursor solution A and precursor solution B, wherein the precursor solution A includes solute A and solvent A, and the precursor solution B includes solute B and solvent B, wherein the solute A includes at least one of methylamine halide, formamidine halide, cesium halide and lead halide, the solvent A is 2-methoxyethanol, the solute B includes at least one of cesium halide, lead halide and methylamine halide, and the solvent B includes at least one of acetonitrile, N-methyl-2-pyrrolidone, 1,3-dimethyl-3,4,5,6-tetrahydro-2-pyrimidone, ethanol and 1-cyclohexyl-2-pyrrolidone.

2. The perovskite ink according to claim 1, characterized in that The concentration of the precursor solution A is 0.6-1.6 mol / L; and / or the concentration of the precursor solution B is 0.2-1.2 mol / L.

3. A method for preparing the perovskite ink according to claim 1 or 2, characterized in that: The following steps are involved: Dissolving the solute A in the solvent A to obtain the precursor solution A; Dissolving the solute B in the solvent B to obtain the precursor solution B; The precursor solution A and the precursor solution B are mixed to obtain the perovskite ink.

4. A perovskite solar cell, characterized in that: It comprises a substrate layer, a hole transport layer, an absorption layer, an electron transport layer, a functional layer and an electrode layer which are arranged in sequence, wherein the absorption layer is prepared from the perovskite ink according to claim 1 or 2.

5. The perovskite solar cell according to claim 4, characterized in that: The base layer includes one of a FTO base layer, an ITO base layer and an AZO base layer.

6. The perovskite solar cell according to claim 4, characterized in that: The hole transport layer includes at least one of nickel oxide, phosphoric acid containing a carbazole group, poly(3-hexylthiophene-2,5-diyl), poly(3,4-ethylenedioxythiophene), 2,2",7,7"-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], copper thiocyanate, cuprous oxide, and aluminum oxide.

7. The perovskite solar cell according to claim 4, characterized in that: The component of the absorption layer is FA x Cs y MA (1-x-y) PbI z Br (3-z) ; Among them, x is 0.8-0.98; y is 0.02-0.2; z is 2.5-3.

8. The perovskite solar cell according to claim 4, characterized in that: The electron transport layer includes at least one of C60, PCBM and ICBA.

9. The perovskite solar cell according to claim 4, characterized in that: The functional layer includes at least one of BCP, SnO2, ZnO, Al2O3 and LiF.

10. A method for preparing a perovskite solar cell according to any one of claims 4 to 9, characterized in that: The following steps are involved: Prepare the hole transport layer on the surface of the substrate layer; Prepare the absorption layer on the surface of the hole transport layer; Preparing the electron transport layer on the surface of the absorption layer; Preparing the functional layer on the surface of the electron transport layer; The electrode layer is prepared on the surface of the functional layer to obtain the perovskite solar cell.

Citation Information

Cited By

  • Perovskite precursor solution, perovskite solar cell and preparation method thereof

    CN119907612A

  • Nanometer flower-shaped poly (9-hydroxyfluorene) / NiO composite material and preparation method and application thereof

    CN120221296A

  • Perovskite ink

    WO2026167376A1